A comparison of positive and negative reinforcement for compliance to treat problem behavior maintained by escape. Issue 3 (13th May 2015) - Slocum, Sarah K.; Vollmer, Timothy R.
<x xml:space="preserve">Abstract</x> Previous research has shown that problem behavior maintained by escape can be treated using positive reinforcement. In the current study, we directly compared functional (escape) and nonfunctional (edible) reinforcers in the treatment of escape‐maintained problem behavior for 5 subjects. In the first treatment, compliance produced a break from instructions. In the second treatment, compliance produced a small edible item. Neither treatment included escape extinction. Results suggested that the delivery of a positive reinforcer for compliance was effective for treating escape‐maintained problem behavior for all 5 subjects, and the delivery of escape for compliance was ineffective for 3 of the 5 subjects. Implications and future directions related to the use of positive reinforcers in the treatment of escape behavior are discussed.